Fabrication of gum arabic-graphene (GGA) modified polyphenylsulfone (PPSU) mixed matrix membranes: A systematic evaluation study for ultrafiltration (UF) applications - Ali, Alaa Mashjel; Rashid, Khalid T.; Yahya, Ali Amer; Majdi, Hasan Sh.; Salih, Issam K.; Kamal, Yusoh; Alsalhy, Qusay F.; AbdulRazak, Adnan A.; Figoli, Alberto (MDPI, 2021)
In the current work, a Gum, Arabic-modified Graphene (GGA), has been synthesized via a facile green method and employed for the first time as an additive for enhancement of the PPSU ultrafiltration membrane properties. A series of PPSU membranes containing very low (0–0.25) wt.% GGA were prepared, and their chemical structure and morphology were comprehensively investigated through atomic force microscopy (AFM), Fourier transforms infrared spectroscopy (FTIR), X-ray diffraction (XRD), and field emission scanning electron microscopy (FESEM). Besides, thermogravimetric analysis (TGA) was harnessed to measure thermal characteristics, while surface hydrophilicity was determined by the contact angle. The PPSU-GGA membrane performance was assessed through volumetric flux, solute flux, and retention of sodium alginate solution as an organic polysaccharide model. Results demonstrated that GGA structure had been successfully synthesized as confirmed XRD patterns. Besides, all membranes prepared using low GGA content could impart enhanced hydrophilic nature and permeation characteristics compared to pristine PPSU membranes. Moreover, greater thermal stability, surface roughness, and a noticeable decline in the mean pore size of the membrane were obtained.